NT-proBNP trajectory after transcatheter aortic valve replacement and its association with 5-year clinical outcomes - Zhou, Yaoyao; Zhu, Qifeng; Hu, Po; Li, Huajun; Lin, Xinping; Liu, Xianbao; Pu, Zhaoxia; Wang, Jian’an (Frontiers in Cardiovascular Medicine, 2023)
Background There is little evidence of evolution in NT-proBNP after transcatheter aortic valve replacement (TAVR) in aortic stenosis (AS) patients. Additionally, less is known about the prognostic value of NT-proBNP trajectory following TAVR. Objectives This study aims to investigate short-term NT-proBNP trajectory following TAVR and explore its association with clinical outcomes in TAVR recipients. Methods AS patients undergoing TAVR were included if they had NT-proBNP levels recorded at baseline, prior to discharge, and within 30 days after TAVR. We used latent class trajectory models to identify NT-proBNP trajectories based on their trends over time. Results Three distinct NT-proBNP trajectories were identified from 798 TAVR recipients, which were named class 1 (N=661), class 2 (N=102), and class 3 (N=35). Compared to those with trajectory class 1, patients with trajectory class 2 had a more than 2.3-fold risk of 5-year all-cause death and 3.4-fold risk of cardiac death, while patients with trajectory class 3 had a more than 6.6-fold risk of all-cause death and 8.8-fold risk of cardiac death. By contrast, the groups had no differences in 5-year hospitalization rates. In multivariable analyses, the risk of 5-year all-cause mortality was significantly higher in patients with trajectory class 2 (HR 1.90, 95% CI 1.03 - 3.52, P = 0.04) and class 3 (HR 5.70, 95% CI 2.45 - 13.23, P <0.01). Conclusions Our findings implied different short-term evolution of NT-proBNP levels in TAVR recipients and its prognostic value for AS patients following TAVR. NT-proBNP trajectory might add more clinical implications apart from its baseline level. It is constructive for clinicians regarding patient selection and risk prediction in TAVR recipients.